Taxonomische Notiz zu Aculepeira lapponica (Arachnida: Araneae: Araneidae) - Blick, Theo; Nentwig, Wolfgang (Arachnologische Mitteilungen, 2003)

(untitled)
Caused by a similarity with the type species Aculepeira packardi and with A. ceropegia we confirm the combination Aculepeira lapponica for the arctic araneid Aranea lapponica Holm, 1945